TH1/TH2 pattern of renal tissues in acute and chronic animal models treated with mesenchymal stem cells - Semedo, Patricia; Palasio, Carolina Gardini; Oliveira, Cassiano Donizetti; Feitoza, Carla Quarim; Gonçalves, Giselle Martins; Wang, Pamella Mei; Cenedeze, Marcos Antonio; Pacheco-Silva, Alvaro; Teixeira, Vicente de Paula; Reis, Marlene Antônia dos; et al. (Brazilian Journal of Transplantation, 2007)
Mesenchymal stem cell (MSC) therapy is a promising new therapy for kidney diseases. Many authors have been demonstrated that the MSC treatment leads to N improvement of the renal function in acute damaged models. However, the way it works still remains elusive. Purpose: To evaluate whether the renal protection provided by MSC administration seen in acute and chronic renal remnant damaged models involves modulation of the inﬂammation. Methods: MSC were attained from bone marrow of male Wistar rats. Female Wistar were subjected to ischemia-reperfusion damage by clamping renal pedicles for 1 hour. After a 6h reperfusion, 2.105 MSC were administrated i.v. in the chronic model. The nephrectomy models 5/6 were treated with 1.106 MSC administered i.v. after two weeks. Results: After a 24h reperfusion, MSC-treated animals presented a signiﬁcant improvement of the renal function associated to decreased levels of IL-1β, IL-6 and TNF-α gene expression. Interestingly, the IL-4 mRNA expression increased in parallel. Furthermore, a higher expression of PCNA and an increase in the Bcl2/Bad ratio were seen in kidney tissues of MSC-treated animals. In the remnant model, this modulation in the cytokine pattern was sustained, despite a lack of amelioration of the renal dysfunction. Moreover, the expressions of TGF-β, MMP-9, TIMP-1 and Smad7 were not altered, although PAI-1 was signiﬁcantly decreased. Conclusion: MSC therapy can indeed modulate the inﬂammatory response following acute and chronic renal injuries, accelerating the tubular repair; however, long-term outcomes seem not to be halted by this therapy.